The Impact of Exclusion Criteria on a Physician’s Adenoma Detection Rate - Marcondes, Felippe O. (Gastrointest Endosc, 2015)
BACKGROUND: The adenoma detection rate (ADR) is a validated and widely used measure of colonoscopy quality. There is uncertainty in the published literature on which colonoscopy examinations should be excluded when measuring a physician’s ADR. OBJECTIVE: To examine the impact of varying the colonoscopy exclusion criteria on physician ADR. DESIGN: We applied different exclusion criteria used in 30 prior studies to a dataset of endoscopy and pathology reports. Under each exclusion criterion, we calculated physician ADR. SETTING: A private practice colonoscopy center affiliated with the University of Illinois College of Medicine. PATIENTS: Data on 20,040 colonoscopy examinations and associated pathology notes performed by 11 gastroenterologists from July 2009 to May 2013. MAIN OUTCOME MEASUREMENTS: ADR across all colonoscopy exainations, each physician’s ADR, and ADR ranking. RESULTS: There were 28 different exclusion criteria used when measuring ADR. Each study used a different combination of these exclusion criteria. The fraction of all colonoscopy examinations in the dataset excluded under these combinations of exclusion criteria ranged from 0 to 93.1%. The mean ADR across all colonoscopy examination was 35.9%. The change in mean ADR after applying the 28 exclusion criteria ranged from −4.6 to +3.1 percentage points. However, the exclusion criteria impacted each physician’s ADR relatively equally, and therefore physicians’ rankings via ADR were stable. LIMITATIONS: ADR assessment was limited to a single private endoscopy center. CONCLUSIONS: There is wide variation in the exclusion criteria used when measuring ADR. Although these exclusion criteria can impact overall ADR, the relative rankings of physicians by ADR were stable. A consensus definition on which exclusion criteria are applied when measuring ADR is needed.